Staging history (Leiden ; Boston)
ix, 277 sayfa
Keywords: “Staging History unites essays by nine specialists in the field of late medieval and early Renaissance drama. Their focus is on English, Dutch and Humanist German drama, as well as on a modern Swiss adaptation of Shakespeare's Henry V. Featuring prominently in this book are plays by, among others, John Bale, Jacob Schoepper, Johannes Agricola and Jacob Duym. Special attention is also paid to the Croxton Play of the Sacrament and the Dutch abele spelen. So far this topic has not received wide attention within the world of medieval and early Renaissance studies. This exploration aims at arousing more interest in this field by scholars working on European drama from the late Middle Ages and the early Renaissance.“ --